Polyaniline Derivatives for Chemical Sensors of Ammonia Vapor - R. B. Salikhov; A. A. Gaskarova; T. R. Salikhov; A. D. Ostaltsova; T. T. Yumalin (Chemistry Proceedings)
This study considers the possibility of using thin films of new soluble modified polyaniline derivatives in the creation of chemical sensors. The study involves an examination of how the current passing through resistive structures, which are constructed using thin films of polyanilines, is influenced by varying concentrations of ammonia vapors present in the surrounding air.